Observations on Sex Ratios, Sexual, Dimorphism, Weight and moisture-Content in Two Termites From Indian Desert, Miorocerotermes Raja And Miorotermes obesi ( Termitidae) - Roonwal, M L; Verma, S C (Annals of Arid Zone, 2016)
1. Microcerotermes raja Roonwal and Bose (Amitermitinae): Sex rations: Among 365 swarming imagoes, the females predominate in the ratio ♂ 2 : ♀ 3 (range, ♂38.5-52.9 percent, ♀ 47. 1-61,5percent). Sexual dimorphism (body-size) : Females are somewhat longer than males in respect of total length (with and without wings). The sexes do not differ in respect of the maximum width of head (with eyes) and the maximum width of abdomen. 2. Microtermes obesi Holmgren (Macrotermitinae) : Sex ratios: Among 950 swarming imagoes the range is: ♂ 48.8-62 percent, ♀ 38-51.2 per cent. The chi-square value is 15.66(highly significant) ; the sex ratio is not predictable and may vary with place and time of swarming. Sexual dimorphism (body-size) : Females are distinctly larger than males in regard to the total length (with wings) and the maximum width of abdomen; but the sexes do not differ in regard to the total length (without wings) and the maximum width of head (with eyes). Body weight. etc.: Mean wet weight: ♂13.95,♀ 18.26mg.; females are distinctly heavier (ca. 31 per cent) than males. Mean dry weight: ♂ 7.96, ♀ 9.60 mg.; females are distinctly heavier (ca. 20.6 percent) than males. Moisture content: Mean ♂ 43.17 per cent, ♀ 43.8 per cent; the sexes do not differ significantly.